Художественное наследие англии в обучении английскому языку (SCIENCE and SOCIETY, 2020)
The article deals with the pedagogical system of studying by students the literary — artistic heritage of England at extracurricular clas- ses. The author characterizes the content of components of the pedagogical system and stages of studying the literary-artistic creation of